Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.5 - Rationalizing Numerators and Denominators of Radical Expressions - Exercise Set - Page 718: 32



Work Step by Step

$\dfrac{3}{\sqrt{7}-4}$ Multiply the numerator and the denominator of this expression by the conjugate of the denominator and simplify: $\dfrac{3}{\sqrt{7}-4}=\dfrac{3}{-4+\sqrt{7}}\cdot\dfrac{-4-\sqrt{7}}{-4-\sqrt{7}}=\dfrac{3(-4-\sqrt{7})}{(-4)^{2}-(\sqrt{7})^{2}}=...$ $...=\dfrac{3(-4-\sqrt{7})}{16-7}=\dfrac{3(-4-\sqrt{7})}{9}=\dfrac{-4-\sqrt{7}}{3}=-\dfrac{\sqrt{7}+4}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.